Kunlun Nu: Translation and Character Analysis of a Tang Dynasty Martial Arts Classic - Yingying, Liu; Teh, Wan Hasmah Wan (Journal of Posthumanism, 2025)
This article presents a groundbreaking English semantic translation of the classic ancient literary novel Kunlun Nu, a martial arts work by Pei Xing, a renowned writer of the Tang Dynasty. The study employs quantitative analysis using the time series method to examine the character images in the English semantic translation of Kunlun Nu. A bubble diagram, a key descriptive tool in time series analysis, is utilized to analyze three variables: Plot, Positive and Negative Image, and Quantity of Character Qualities. This framework is applied to the four main characters of Kunlun Nu, assessing them in terms of the quantity of character qualities (flat characters or round characters), character development dynamics (static characters or developmental characters), and character impact (protagonist and antagonist). The results provide a comprehensive analysis of character portrayal and development in this seminal work. The findings offer fresh insights into the complexities of character roles and relationships in Kunlun Nu, contributing to a deeper understanding of the narrative's structural and thematic intricacies in translation.